Volume Change and Strength Behavior of Expansive Clay Stabilized with Scrap Tire Rubber - Hamza, Araz Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Expansive soils in semi-arid climates are well known to cause detrimental damages in the form of cracks and differential movements of the civil engineering structures. In quest for economical and efficient methods for mitigation of swelling soils, there is a growing interest in using waste materials with a secondary aim of recycling the material. This study concentrated on using scrap tire rubber (STR) powder as a stabilizer for improving the locally available expansive soil. Using the scrap tire rubber in soil stabilization can be a feasible solution for recycling this waste material, hence reducing the environmental problems, as discarded waste tires impose a major environmental pollution. An experimental program was conducted to evaluate the mechanical characteristics of the expansive soil, including swell-shrinkage potential, hydraulic properties, and strength characteristics. Different percentages of STR (10%, 20%, and 30%) were mixed with natural expansive soil to evaluate its influence on physical and mechanical properties. The experimental findings displayed that 30% STR reduced the plasticity and swell potential considerably, while no change in compressibility parameters was recorded. The STR inclusion has been most effective in rendering the shrinkage potential, which causes settlement of light structures along their outer perimeter causing differential movements. Finally, the results show that modification of expansive soils using STR might be an effective technique in enhancing the soil characteristics against swelling-shrinking potential of subsoils on which roads and light weight structures are constructed. Therefore, the scrap tire rubber waste has a potential for stabilizing expansive soils, thus giving a two-fold advantage in enhancing a problematic soil and also resolving the problem of disposal of waste by recycling it. On the other hand, the results of unconfined compression, flexural strength and California Bearing Ratio tests demonstrated that the amounts and particle size of STR could not improve the strength properties, and that further research is recommended using different sizes and percentages of the scrap tire rubber waste. Keywords: Expansive soil, scrap tire rubber and stabilization.

ÖZ: Yarı-kurak iklimlerde, şişen zeminlerin yapılarda, çatlaklara ve farklı hareketlere neden olan önemli hasarlara neden olduğu iyi bilinmektedir. Ekonomik ve etkin iyileştirme metodu arayışı içerisinde, ikincil bir hedef olarak geri dönüşümün de sağlanması amaçlanan, atık kullanımına önemli bir ilgi artışı vardır. Bu araştırmada atık kauçuk tozu kullanılarak yerel bir şişen zeminin iyileştirilmesi çalışılmıştır. Zemin stabilizasyonunda atık kauçuk kullanımı, bu atık malzemenin çevreye verebileceği önemli kirlilik ve hasarın islahı için kolay bir geri dönüşüm yöntemi olabilecektir. Bu deneysel çalışmada şişen zeminin mekanik davranışı şişme-büzülme, kompresibilite, dayanım ve hidrolik özelliklerin irdelenmesi ile çalışılmıştır. Farklı kauçuk tozu yüzdelikleri (%10, %20, %30) karıştırılarak şişen zeminin değişen fiziksel ve mekanik davranışı çalışılmıştır. Deney bulguları %30 kauçuk tozunun plastisiteyi ve şişme potansiyelini önemli miktarda düşürdüğünü, ancak kompresibilitenin bu katkıdan etkilenmediğini göstermiştir. Ayrıca, kauçuk tozu katkısı büzülme potansiyelini düşürmede çok etkili olmuştur. Büzülme potansiyeli özellikle hafif yapıların çevresinde iklimsel etkenlerle zeminin büzülmesiyle temellerde oturmalara neden olur. Sonuç olarak, kauçuk tozu kullanımının hafif yapıların altındaki şişen-büzülen zeminlerin iyileştirilmesinde oldukça etkili olabileceği, aynı zamanda bu malzemenin geri dönüşümünün de sağlanmış olacağı görüşüne varılmıştır. Ancak, dayanım deneyleri olan serbest basınç, eğilme ve CBR sonuçları kullanılan malzemenin mukavemet açısından yeterli olmadığını göstermiştir. Dolayısıyla farklı boyutlarda kesilmiş kauçuk parçaları ve farklı miktarlarla daha detaylı bir araştırma yapılması tavsiye edilmektedir. Anahtar kelimeler: Şişen zemin, stabilizasyon, atık kauçuk.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assoc. Prof. Dr. Huriye Bilsel.
Keywords: Civil Engineering; Soil Mechanics; Expansive soil; scrap tire rubber and stabilization